Critical success factors of the challenges in providing quality education: a study on Malaysian private higher learning institutions - Islam, Rafikul (The Creative Decisions Foundation, 2015)
The issue of quality education in higher learning institutions is timely and crucial due to the government’s aspiration to turn Malaysia into a centre of educational excellence in the Asian region. Quality education acts as an indicator of the institution’s ability to provide tertiary education to the society as well as an instrument for the nation’s economic growth. To date, numerous studies have been conducted to measure the quality of education in higher learning institutions in Malaysia. However, the task of identifying the challenges faced by these institutions in providing quality education and the critical success factors to address the challenges has largely been ignored by previous researchers. It is within this overall context that the study employs the Analytic Hierarchy Process, with the aim of identifying and ranking the challenges and also their critical success factors. Data was collected from the stakeholders of Malaysian private HLIs via semi structured interviews and a questionnaire survey. Results indicate that ‘Establishing financial capabilities for the institution’s self-sustainability’, ‘Complying with the rules and regulations of regulatory agencies and relevant professional bodies’ and ‘Providing facilities to ensure the delivery of quality education’ are the challenges that need to be carefully managed by the management of these Malaysian private HLIs. Critical success factors that act as practical solutions to address each challenge were also identified and ranked in this study.